Calidad de servicio y satisfacción de los clientes de la empresa Star Motor Selva E.I.R.L. Iquitos 2022 - Chota Pimentel, Reyna (2023)
The purpose of this work is to investigate the relationship between service quality and customer satisfaction at Star Motor Selva, an Iquitos 2022 spare parts distributor. It has a quantitative approach and a non-experimental design. The population and sample consisted of 30 consumers. Star Motor Selva has a mean score of 0.867** and a sigma value of 0.000 (two tails), concluding that there is a significant relationship between service quality and customer satisfaction.